Using Discovery Learning to Encourage Creative Thinking - Mardia Hi. Rahman (International Journal of Social Sciences & Educational Studies, 2017)
Creative thinking ability development is needed to be implemented by every educator including lecturers to their students. Therefore, they need to seriously act and design their learning process. One of the ways to develop student’s creative thinking is using discovery learning model. This research is conducted in physics education study program in 2016 with students who took learning and teaching class as research subject. From the research analysis result and discussion, it can be concluded that discovery learning model can encourage students’ creative thinking ability in learning and teaching strategy subject.